Al-Dakhīl alladhī Raddahu al-Brūfīsūr al-Duktūr al-Ḥājj ʿAbd al-Mālik Karīm Amrullāh al-Mulaqqab bi-"Ḥāmkā" fī Tafsīrih "Al-Azhar": Dirāsah Taḥlīliyyah Naqdiyyah fī Sūrat al-Baqarah - Muhammad Irfan; Mahmoud Ahmed Mahmoud Mashour (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
Tafsir al-Azhar by Hamka (Prof. Dr. Haji Abdul Malik Karim Amrullah) stands as one of the most influential contemporary Qur'anic commentaries in Indonesia and Southeast Asia, widely recognized for its balanced methodology and reform-oriented perspective. Nevertheless, no exegetical work is entirely immune from al-dakhīl — spurious or extraneous interpretive materials that have infiltrated the tafsir tradition. This reality demands critical scrutiny of how exegetes identify, evaluate, and reject such materials. This study aims to identify instances of al-dakhīl explicitly rejected by Hamka in Tafsir al-Azhar within Sūrat al-Baqarah, and to analyze the scholarly principles underlying his rejection. An inductive method was employed to inventory relevant cases, complemented by a critical analytical approach to examine the rejected narratives and opinions alongside their academic justifications. The findings reveal that the al-dakhīl rejected by Hamka encompasses Isrāʾīliyyāt traditions, weak narrations, mythological stories, and interpretations derived from unreliable or non-Islamic sources. In evaluating these materials, Hamka consistently applied two primary criteria: conformity with the Qur'an and authenticated Sunnah, and coherence with sound reasoning and established principles of Qur'anic exegesis. This study underscores the critical-evaluative dimension of Hamka's exegetical methodology and his contribution to purifying the tafsir tradition from interpretively unsound materials. The findings enrich contemporary scholarship on exegetical criticism and al-dakhīl studies within the Indonesian Qur'anic interpretive tradition.